Effects of nitrogen fertilizer on structure and physicochemical properties of 'super' rice starch. (1st July 2020) - Zhou, Tianyang; Zhou, Qun; Li, Enpeng; Yuan, Limin; Wang, Weilu; Zhang, Hao; Liu, Lijun; Wang, Zhiqin; Yang, Jianchang; Gu, Junfei
Highlights: Nitrogen treatment decrease ratio of amylose to amylopectin. Moderate nitrogen rate increases proportion of short branch-chain of amylopectin. Moderate nitrogen rate decreases starch gelatinization temperature & enthalpy change. Moderate nitrogen rate increases the viscosity of starch paste. Moderate nitrogen rate increases the eating quality of cooked rice starch. Abstract: Nitrogen fertilizer is an essential nutrient for rice ( Oryza sativa L.), especially, for newly bred 'super' rice cultivars with great yield potential. The effects of nitrogen fertilizer (0, 100, 200, 300, 400 kg N ha −1 ) on the physicochemical properties of two high yielding 'super' rice Yongyou 2640 and Lianjing 7 were investigated in this study. The application of nitrogen fertilizer affects the structure of rice starch, thus changing its functional properties, which ultimately leads to a change in the quality of both rice cultivars. There were dose effects of nitrogen fertilizer on grain quality. Grain quality was improved under moderate nitrogen inputs (100 & 200 kg N ha −1 ), but deteriorated at excessive nitrogen levels (300 & 400 kg N ha −1 ). With moderate N application, starch granule size increased and the surface of starch granule became smoother; there were higher proportion of short branch-chain of amylopectin and lower proportion of long branch-chain of amylopectin with low relative crystallinity, lower degree of order of structure and higher content of amorphous structure at the outer region of the starch granules; peak viscosity, hot viscosity, breakdown value were increased while setback and pasting temperature were decreased; gelatinization temperature, gelatinization enthalpy, retrogradation enthalpy, retrogradation percentage, hardness were decreased while viscosity were increased. At excessive nitrogen inputs, the grain quality was deteriorated and the opposite results of structure and physicochemical properties of rice starch were observed. These results indicate that nitrogen fertilizer significantly affected the structure and physicochemical properties of rice starch, and appropriate fertilization would improve rice grain quality.